WASIAT WAJIBAH UNTUK ANAK ANGKAT MENURUT IMAM MADZHAB DAN HUKUM POSITIF DI INDONESIA - Misno (JURNAL ALAMIAH, 2021)
Islamic law is a perfect legal system, it regulates all aspects of human life, from state affairs to individual and family matters. In family matters it has been regulated in detail regarding the division of inheritance, each family member who becomes the heir has been assigned the parts. However, not all families are blessed with children, so some married couples take a child to be adopted. What is the position of adopted children in Islamic law? And whether he inherited from his adoptive parents. Based on the syar'i texts originating from the Al-Qur'an and As-Sunnah, it is not found explicitly regarding inheritance for adopted children, but implicitly the spirit of Islam always protects every child who still needs protection and care. Therefore, Islamic jurists have formulated a mandatory will for adopted children. Wasat obligatory is a will determined by an imam (head of state) for the inheritance of someone who has adopted children who still need to be cared for. The size of the obligatory will, as in general wills, should not be more than 1/3 of the total inheritance. Some of the conditions related to the implementation of the obligatory will are that the adopted child still needs money for his daily needs.